Social theory for social work : ideas and applications - Thorpe, Christopher (Student social work, 2018)
Trying to understand how the world looks through the eyes of individuals and groups and how it shapes the ways they think and act is something social workers do all the time. It is what social theorists do too. This book identifies and explains in a highly accessible manner the absolute value of social theory for social work. Drawing on the theoretical ideas and perspectives of a wide range of classical and modern social theorists, the book demonstrates the insights their work can bring to bear on a wide range of social work practice scenarios, issues and debates.